The Role of Microfinance in Poverty Alleviation in Malaysia With Reference to Millennium Development Goals - Heile, Abdirahim Ibrahim Sheik (2011)
Microfinance can be a significant aspect of a useful poverty reduction approach particularly for developing countries. The services supplied by microfinance institutions can enable the poor to flatten their expenses, run their menace improved, construct their capital progressively, expand their business enterprises, improve their gross income potential, and have a better quality of life. This paper is about microfinance institutions and their role of poor people with the focusing in the northern Malaysia. I mainly concise my paper through client’s (the poor people, who borrowed loan from microfinance institutions) perspective and build up my research based on it. The first objective of this paper is to examine the extent to which Microfinance Institutions (MFIs) contribute to poverty reduction in northern Malaysia (Kedah). The second objective is to find out role of microfinance in poverty reducing, with examining the achievements and performances of MDGs, in addition how MFIs affects the living standard (income, saving, education, health and empowerment) of the poor people in Kedah. Subsequent the information collected from microfinance clients, it was discovered that MFIs have changed the life of poor people in a positive way. MF clients have increased their incomes, capital invested and thus growth of their businesses. In spite of these accomplishments 180 questionnaires have been distributed to the microfinance clients in northern region in Malaysia (Kedah), it was additional study that some conditions like living standards, empowerment and poverty alleviation of Poor People. However, all 180 of them were returned and usable for analysis. Standard or simultaneous regression analysis is performed to test the hypotheses of the study. The findings are discussed and recommendations for the future research have been addressed.